Increasing oilseed production through cluster demonstration in Patna district: A case study (Journal of Oilseed Brassica, 2026)
Cluster Frontline Demonstration was conducted to study the impact of improved cultivar, seed treatment, sulphur application, diseases and pest management on production as well as productivity of linseed and mustard. Results revealed that Shekhar variety of linseed performed better as compared to local variety with 28.6 % yield gap between both the varieties. Similarly, RNG-48 of Indian mustrad recorded 32.0 % higher seed yield compared to local variety. Therefore, the results clearly indicates that the use of improved varieties with scientific package and practices under Cluster Frontline Demonstration programme can play a key role in improving the seed yield of oilseeds and will significantly contribute to increase the productivity of oilseeds in Bihar state.